Traditional processes of food products bio conservation based on plants extracts in south and central-Benin - GANDEHO, Justin G.; TCHEKESSI, C. K. Célestin; BELLO, Daouda O.; EDIKOU, Spéro K. U.; ATCHOUKE, Laurent G. D.; AYENA, Aimé-Césaire; BOKOSSA, Innocent Y.; DOSSOU, JOSEPH (My University, 2022)
This study aims to diagnose the traditional processes of bio conservation of food products based on plant extracts. A semi-structured survey was conducted among 240 state and private actors in agricultural and citrus production and practitioners of this method of conservation in the communes of Za-Kpota and Klouékanmè in Benin. The data collected (type of conservatives, plant used, products conserved, production technology of the bioconserver) were subjected to a descriptive analysis and analysis of variance (ANOVA) followed by the Student Newman Keuls test at 5%. The results indicate that the respondents in the commune of Za-Kpota are (p<0.05) the oldest (43.32±2.03 years). In all survey areas, orange and chili are the plants most used for post-harvest conservation (43.8%). Chili fruits combined with orange peels are frequently used for the conservation of harvested products (56%) and the products conserved are mainly cowpeas (37.9%), maize (26.2%) and groundnuts (15.4%). The conservatives used to control pests are introduced at the beginning and end of the drying process before the commodities are put into storage. Conservatives operate most often by repulsion (57.1%). The maximum duration of harvested products using conservatives is three months (67.1%) and 73.8% of stored products are accepted by consumers. It is therefore necessary to define the production parameters of orange tree-based bioconservatives in order to optimize this technology.
Keywords: Bio preservation; Post-harvest; Agricultural products; Citrus fruit; Peelings